Use of ozone as a complementary therapy in dentistry. Literature review - Concha-Saavedra, Karen (2022)
Since the discovery of ozone, it has been extensively investigated, proving effective in treating infections in different health professions, and also in dentistry. The objective of this article is to review the evidence regarding the use of ozone as a supplement in the treatment of periodontal diseases. Ozone reduces the number of bacteria, their reproductive capacity and even achieving their complete disappearance, in addition to having action against viruses and fungi. Thanks to this, its use as an adjuvant irrigant is currently being discussed, mainly because it is a biocompatible, highly effective antimicrobial agent, with oxidative potential that accelerates the physiological healing process, analgesic effect, and after characteristics such as its easy obtaining and mode of administration. However, ozone must be used in adequate concentrations, since an excess of it can cause the total elimination of any organism, thus it must be administered through the adequate routes and as complementary therapy.